1995
DOI: 10.1128/iai.63.3.799-803.1995
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of human interleukin 2 by recombinant Mycobacterium bovis BCG

Abstract: The human interleukin 2 (huIL-2) gene was introduced into Mycobacterium bovis BCG by using the integrative vector pMV306. To express and secrete huIL-2 from BCG, two different plasmids, CI and CII, were made. In CI, the huIL-2-encoding region was under the control of the ␣-antigen promoter of BCG; in CII, the expression of huIL-2 was regulated by the heat shock protein 60 promoter. A signal peptide sequence isolated from the naturally secreted ␣-antigen of BCG was inserted between the promoter and huIL-2-encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…This would create a microenvironment that favours development of a type 1 immune response. In our experience and that of others, 24 , 25 rBCG/IL‐2 is eliminated at the same rate, if not slightly more rapidly, than normal BCG in vivo and is unlikely to contribute to the results observed 16 weeks later in the vaccine response. This is supported by our inability to culture rBCG/IL‐2 from spleen samples taken 16 weeks after subcutaneous vaccination (unpubl.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This would create a microenvironment that favours development of a type 1 immune response. In our experience and that of others, 24 , 25 rBCG/IL‐2 is eliminated at the same rate, if not slightly more rapidly, than normal BCG in vivo and is unlikely to contribute to the results observed 16 weeks later in the vaccine response. This is supported by our inability to culture rBCG/IL‐2 from spleen samples taken 16 weeks after subcutaneous vaccination (unpubl.…”
Section: Discussionsupporting
confidence: 61%
“… 22 , 23 , 24 Further, it has been shown that IL‐2 secreted from BCG can induce upregulation of antigen‐specific IFN‐γ production by splenocytes restimulated in vitro. 11 , 25 We have extended these findings to show that cytokines secreted by BCG can modulate immune responses to vaccination in BALB/c mice. This confirms our earlier findings that IL‐2 is able to modulate the immune responses of a naturally susceptible host species (deer) to BCG vaccination 24 .…”
Section: Discussionmentioning
confidence: 80%
“…We assembled a series of constructs to complement the Δ( furA–katG ) mutant strain NCGM2836 with pMV306 (Fig. 1B and C), by site‐specific integration into the chromosomal attB site (Stover et al ., 1991; Kong and Kunimoto, 1995). The constructs had no furA–katG (NCGM2836/Vector); or furA–katG harbouring no mutation (NCGM2836/WT), furA c41t (NCGM2836/ furA c41t ), Int g‐7a (NCGM2836/Int g‐7a ), Int a‐10c (NCGM2836/Int a‐10c ) or Int g‐12a (NCGM2836/Int g‐12a ).…”
Section: Resultsmentioning
confidence: 99%
“…The construction of the pknF ( Rv1746 ) null strain ( ΔpknF ) was described previously (Spivey et al ., ); this has an in‐frame unmarked deletion to avoid downstream polar effects on the Rv1747 gene. For complementation of the pknF deletion, the genes pknF , 609 bp of Rv1745c and 20 bp of Rv1747 were amplified by PCR (Spivey et al ., ) and the product cloned into the vector pKP186 (Rickman et al ., ), a pMV306 (Kong & Kunimoto, ) derivative lacking the integrase gene and electroporated into the ΔpknF mutant along with the mycobacterial suicide vector, pPS‐Int containing the integrase gene (Springer et al ., ; Curry et al ., ). Construction of the hygromycin‐marked Rv1747 deletion mutant was described previously (Curry et al ., ).…”
Section: Methodsmentioning
confidence: 99%